Processing words in two languages: An event-related brain potential study of proficient bilinguals - Geyer, Alexandra (2011)
In a previous study of native-English speaking university learners of a second language (Spanish) we observed an asymmetric pattern of ERP translation priming effects in L1 and L2 (Alvarez et al., 2003, Brain & Language, 87, 290-304) with larger and earlier priming on the N400 component in the L2 to L1, compared with the L1 to L2 direction. In the current study 20 native-Russian speakers who were also highly proficient in English participated in a mixed language lexical decision task in which critical words were presented in Russian (L1) and English (L2) and repetitions of these words (within and between languages) were presented on subsequent trials. ERPs were recorded to all items allowing for comparisons of repetition effects within and between (translation) languages. The results revealed a symmetrical pattern of within-language repetition and between-language translation ERP priming effects, which in conjunction with Alvarez et al (2003), supports the hypothesis that L2 proficiency level rather than age or order of language acquisition is responsible for the observed patterns of translation priming. The ramifications of these results for models of bilingual word processing are discussed.